Bank lending, liquidity regulation and unconventional monetary policies in the Eurozone - Casu, Barbara; Chiaramonte, Laura; Cucinelli, Doriana (Journal of Financial Intermediation, 2026)
We evaluate the joint impact of structural liquidity regulation and unconventional monetary policy on Eurozone banks’ lending. Using an extensive bank-level quarterly dataset from 2008 to 2020, we study the introduction of the Net Stable Funding Ratio (NSFR) under Basel III and the European Central Bank’s Longer-Term Refinancing Operations (LTROs) and Targeted LTROs (TLTROs). We find that while the NSFR had no effect on aggregate lending, it led to an increase in short-term lending and a reduction in long-term lending, consistent with lower maturity transformation. LTRO participation is associated with higher medium- and long-term lending, and our results indicate that this effect is conditional on banks’ structural liquidity positions: banks with rising NSFRs were able to use LTRO and TLTRO funding to sustain long-term credit supply. These findings suggest that central bank liquidity interventions can mitigate the adjustment costs of tighter liquidity regulation during the transition period, enabling banks close to regulatory compliance to maintain longer-maturity lending.